Kinetics of Thermal Degradation of Intumescent Coated Cotton Fabric - DAHIYA, J.B.; KUMAR, KRISHAN (Asian Journal of Chemistry, 2010)
The kinetics for thermal decomposition of coated cotton fabric sample coated with intumescent-nanoclay (CCF-Int-NC) formulation has been carried out to understand the flame retardant potential of the cotton sample. The Coats-Redfern method, Ozawa-Flynn-Wall (OFW) and modified Coats-Redfern methods have been applied on dynamic TG experiments at different heating rates. The random nucleation (F3) type degradation mechanism is found most probable for CCF-Int-NC in inert atmosphere having activation energy (Ea) in range 143.5-168.6 kJ mol-1 and frequency factor in range ln A = 22-27 min-1 during decomposition process at different heating rates using Coats-Redfern method. The values of activation energy obtained in single heating rate and multi-heating rate methods are found not very far from each other in the conversion range α = 0.3 to 0.5 indicating a similar mechanism operating in this range.